The Prevalence of Metabolic Syndrome in Patients with Euthyroid Autoimmune Thyroiditis - Pamuk, Ömer Arif; Keşkek, Şakir Özgür (Cerrahpaşa Medical Journal, 2020)
Objective: Autoimmune thyroid disease is one of the significant disorders of the thyroid gland and a common cause of primary hypothyroidism. Metabolic syndrome is an important metabolic disorder primarily associated with insulin resistance, diabetes, obesity, dyslipidemia, and hypertension. In this study, we aimed to investigate the frequency of metabolic syndrome and its components in patients with euthyroid autoimmune thyroiditis. Methods: A total of 238 subjects, 134 with euthyroid autoimmune thyroiditis and 104 who were healthy, were enrolled in this retrospective study. National Cholesterol Education Program/Adult Treatment Panel (NCEP-ATP) III criteria were used for the diagnosis of metabolic syndrome. The frequency of metabolic syndrome and its components were compared in both groups. Results: The groups were comparable according to age and sex (p>0.05 for each). Anti-thyroid peroxidase (anti-TPO) and anti-thyroglobulin (anti-Tg) levels were high in patients with euthyroid autoimmune thyroiditis (p<0.001). Although the frequencies of hypertension and hyperglycemia were high in the study group, the frequency of metabolic syndrome was similar in both groups (p>0.05). Conclusion: Although some thyroid diseases had been shown to be associated with metabolic syndrome and its components, no association was found between euthyroid autoimmune thyroiditis and metabolic syndrome in this study. Cite this article as: Pamuk ÖA, Keşkek ŞÖ. The Prevalence of Metabolic Syndrome in Patients with Euthyroid Autoimmune Thyroiditis. Cerrahpasa Med J 2020; 44(1): 35-40.